Structural health assessment of prefabricated concrete elements using Acoustic Emission: Towards an optimized damage sensing tool. (10th May 2019) - Tsangouri, E.; Remy, O.; Boulpaep, F.; Verbruggen, S.; Livitsanos, G.; Aggelis, D.G.
Graphical abstract: Highlights: Innovative prefabricated construction elements designed and tested in service loads. The structural integrity fully assessed by Acoustic Emission (AE) monitoring technique. Cumulative AE hits distribution, Load and Calm ratios indicate progressive damage. Damage classified into concrete cracks and reinforcing rebars deformation/slippage. AE selected as damage sensing tool to be implemented on prefabricated constructions. Abstract: The design feasibility and structural integrity of prefabricated construction elements is assessed (concrete cantilever slab carrying thermal insulation break reinforced with steel/basalt rebars and ultra-high-performance concrete) by performing incremental bending tests. The developed damage mechanisms govern failure, therefore their identification appears crucial: concrete cracking, rebars-concrete interface debonding, rebars slippage, concrete crush under compression. However, the complex fracture cannot be effectively characterized by measuring the deterioration of the mechanical properties. In this study, Acoustic Emission (AE) is applied to highlight internal damage progress. It is found based on cumulative AE hits distribution under incremental load and considering the Kaiser and Felicity effects, damage initiation is identified. The damage severity is quantified using Load/Calm ratios. AE sources localization identifies the moment at which the rebars plastically deform; debond from concrete; slip and when concrete cracks and crushes under compression. The damage mechanisms are discriminated based on acoustic signal features distribution as damage evolves (specifically, average frequency and the ratio of rise time over amplitude). It is shown that AE appears an essential and accurate monitoring method that fully characterizes the damage on complex structures. The promising results open new horizons towards the design of fully autonomous prefabricated elements carrying a smart on-line AE sensing tool.